Peran Pokdarwis Dalam Pengembangan Atraksi Wisata di Desa Wisata Tembi, Kecamatan Sewon - Kabupaten Bantul - Putra, Theofilus Retmana (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
Development of the creative industry in Indonesia is advancing as successfully applied in various sectors, one of them in the tourism sector. Tembi Tourism Village is a form of tourism development through the concept of the creative industries. Main treat of this tourist village is a rich blend of interesting and traditional meaning is presented in the form of synergy between the feel of a quiet rural community with a distinctive local cultures. This tourist village a lot of progress since the establishment Pokdarwis in 2010, where development is most visible in terms of quality and quantity of programs tourist attractions. The development of this tourist attraction is able to attract more tourists, proved that the number of tourists each month travelers could reach 600 when the number of tourists in previous years only reached tens of visitors for each month. Pokdarwis is in charge of organizing all forms of development of tourist attractions which are managed by the local community. The Pokdarwis role was seen in the process of design creation, plan implementation, and management of tourist attractions also involve other parties in it, including the people that the eventualities of some stakeholders is that further strengthens the existence of Village Tourism Tembi to improve the quality and quantity of tourist attractions programa.